Tinjauan Penerapan Sistem Informasi Akuntansi Berbasis SAP PT Sido Muncul Tbk - Irma Lastri, Debora; Putra, Dandi Agustian; Regina Wijaya, Shelin; Lian Seventeen, Winny (Pusat Pengembangan Pendidikan dan Bakat Indonesia/Education and Talent Development Center of Indonesia (ETDC Indonesia), 2026)
Digital transformation has become a strategic necessity for large-scale manufacturing companies facing complex transactions and increasing demands for financial transparency. This Community Service Program aims to analyze and evaluate the effectiveness of an SAP-based Enterprise Resource Planning system in supporting the Accounting Information System at PT Industri Jamu dan Farmasi Sido Muncul Tbk. The program employed a qualitative descriptive approach involving a literature review, field observations, documentation, and assistance for accounting and finance staff, as well as operational data-entry personnel. The results demonstrate that the integration of the Financial Accounting and Controlling modules connects logistics, production, sales, and financial data in real time without requiring repetitive data entry. The system improves transaction-recording accuracy, accelerates financial reporting, reduces the risk of human error, and strengthens internal controls through digital authorization and audit trails. It also enhances corporate governance transparency, supports regulatory compliance as a publicly listed company, and facilitates timely managerial decision-making. Nevertheless, its effectiveness remains influenced by user competence, network and electricity stability, and system maintenance requirements. Therefore, regular training and continuous capacity building are necessary to sustain digital transformation and improve the quality of the company’s financial management.